2010
DOI: 10.2500/ajra.2010.24.3508
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Glutaraldehyde-Modified House Dust Mite Extract in Allergic Rhinitis

Abstract: The findings of this study indicate that allergen injection therapy with modified HDM extract is superior to placebo in allergic rhinitis therapy. The treatment was well tolerated and no serious drug-related AE were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 20 publications
2
48
1
Order By: Relevance
“…Our clinical data are consistent with those obtained by other groups using the same treatment. In a prospective, randomized, double-blind clinical trial comparing the effects of 1 year of SIT with the same extract as we used in our study and placebo treatment, Riechelmann et al [26] showed that SIT performed better than control treatment in reducing symptoms and medication.…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical data are consistent with those obtained by other groups using the same treatment. In a prospective, randomized, double-blind clinical trial comparing the effects of 1 year of SIT with the same extract as we used in our study and placebo treatment, Riechelmann et al [26] showed that SIT performed better than control treatment in reducing symptoms and medication.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, SCIT requires frequent office visits, which might be inconvenient for many patients. Indeed, inconvenience is the most common reason for a patient to discontinue or reject SCIT.…”
mentioning
confidence: 99%
“…The preseasonal schedule is generally performed in patients with pollinosis while the perennial schedule is preferentially used in mite-induced allergic rhinoconjunctivitis and/or asthma. Both preseasonal and perennial immunotherapy with allergoids have been shown to be effective in terms of clinical parameters, including rhinoconjunctivitis and/or asthma symptom and medication scores [10,11,12,13,14,15,16,17,18], conjunctival [10,12], nasal and skin reactivity [13,17,18] as well as the immunological parameters. Moderate reductions in allergen-specific IgE, remarkable increases in allergen-specific IgG1 and IgG4 [10,11,13] and a significant decline in IL-4 levels in allergen-stimulated peripheral blood mononuclear cell culture supernatant have been shown in several studies [13].…”
Section: Introductionmentioning
confidence: 99%